Effect of Fish Oil on Anxiety in Pregnant Women with Gestational Diabetes - Anindyanti, Jerika Yolanda; kundarti, Finta isti; Antono, Sumy Dwi; Wijayanti, Lumastari Ajeng (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2025)
East Java has the fourth-highest number of pregnant women with gestational diabetes mellitus among all provinces in Indonesia. While there were 65 pregnant women at the Kediri District Hospital, there were as many as 57 pregnant women with gestational diabetes mellitus at the Aura Syifa Hospital during the study. Eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) in ω-3 are unsaturated fatty acids recognized as essential for child development and recommended for pregnant and breastfeeding mothers. This study aims to see the effect of fish oil supplementation on anxiety levels in pregnant women with GDM. The fish oil product used is